Dormancia en semillas de papaya cv Maradol Roja durante el almacenamiento - Alonso Esquivel, M.=700 1 Ortiz Lopez, Y.; Ramos Ramirez, R.; Oliva Diaz, H.; Capote del Sol, M.
(Es, En)
Ilus., 22 ref.
Keywords: CARICA PAPAYA; DORMICION; SEMILLA; GERMINACION; HUMEDAD; TEMPERATURA; ALMACENAMIENTO; COSTA RICA; AGRONOMIA MESOAMERICANA